Pengaruh Kinerja Keuangan terhadap Return Saham Perusahaan Food and Beverages di BEI - Pande, I Komang Arta Wibawa; Sudjarni, Luh Komang (E-Jurnal Manajemen; Vol 3 No 3 (2014), 2014)
14.00 Instruments in the capital markets are often used for investing is stock. Investors who want to invest in the shares of a certain profit level of investment is called the stock return . Increase or decrease in the acquisition of the stock return is determined by the investor company's projected financial performance in the financial statements. The purpose of this study to determine the significance of the simultaneous effect of both financial performance and partial that views of the level of liquidity, solvency, profitability, and the market valuation of the stock return on the company's food and beverage sector in Indonesia Stock Exchange from 2007 to 2011. Based on the results of simultaneous testing can be seen that the company's financial performance has a significant impact on stock returns. Meanwhile, through a partial test results show that the only solvency variable has a significant impact on stock returns, while other financial performance variables showed no influence on stock returns . Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman";}
Keywords: stock return, liquidity, solvency, profitability, market valuation